Perawatan Maloklusi Kelas III Skeletal dengan Kombinasi Ortodontik-Bedah Orthognatik - Nia Ayu Ismaniati (Faculty of Dentistry, Universitas Indonesia, 2015)
Non-growing patient with excessive mandible and underdeveloped of the maxilla who classified as a class III skeletal malocclusion often found in the orthodontic daily practice. If they come earlier when potential growth is still left, sometimes growth modification can be applied to prevent further facial deformity (by using extra-oral device, for instance). In non-growing class III malocclusions, treatment alternative may consist of compromised-treatment without concerning an ideal treatment goal. However, with the development of knowledge and skills and with the potential improvement of interspecialistic team-work, nowadays, ideal facial aesthetics become possible. The combined orthodontic-orthognathic surgical treatment alternative to correct skeletal facial deformity may be a better alternative. This treatment changes the hostile environment, so that a more stable treatment result with better facial appearance can be achieved. This poster presents a case report of severe class III skeletal malocclusion whose treted with combined orthodontic-orthognathic surgery. The facial and dental improvements as well as the cephalometric changes are presented. The procedure of treatment and the interspecialistic team-work will also be briefly described.